2016
DOI: 10.1056/nejmoa1515520
|View full text |Cite
|
Sign up to set email alerts
|

Elimination ofTaenia soliumTransmission in Northern Peru

Abstract: BACKGROUND Taeniasis and cysticercosis are major causes of seizures and epilepsy. Infection by the causative parasite Taenia solium requires transmission between humans and pigs. The disease is considered to be eradicable, but data on attempts at regional elimination are lacking. We conducted a three-phase control program in Tumbes, Peru, to determine whether regional elimination would be feasible. METHODS We systematically tested and compared elimination strategies to show the feasibility of interrupting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 26 publications
2
103
0
7
Order By: Relevance
“…The proportion of cases of epilepsy attributed to NCC was reduced from 37% among those diagnosed before the intervention to 14% among those diagnosed following the intervention ( P = .02) . More recently a study in Peru has demonstrated a significant reduction in Taenia cysts in pigs, but there has been insufficient time to demonstrate a reduction in epilepsy . In Africa, community‐directed ivermectin programs have significantly reduced transmission of O. volvulus by black flies, but none has examined the impact on epilepsy incidence or prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of cases of epilepsy attributed to NCC was reduced from 37% among those diagnosed before the intervention to 14% among those diagnosed following the intervention ( P = .02) . More recently a study in Peru has demonstrated a significant reduction in Taenia cysts in pigs, but there has been insufficient time to demonstrate a reduction in epilepsy . In Africa, community‐directed ivermectin programs have significantly reduced transmission of O. volvulus by black flies, but none has examined the impact on epilepsy incidence or prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, The Bill & Melinda Gates Foundation has sponsored a large-scale trial of strategies aimed at eliminating T. solium from a large area of rural Peru. The recently reported results indicated that human MDA (2 g nicolsamide, three rounds per annum) administered in combination with porcine vaccination (TSOL18) and anthelmintic treatment (oxfendazole 30 mg/kg) successfully eliminated T. solium from the porcine intermediate host in 105 of 107 intervention villages, with elimination sustained for at least 1 year post-intervention 123. Recently in southeast Asia, porcine vaccination (TSOL18) and anthelmintic treatment (oxfendazole 30 mg/kg) have been combined with a human MDA program (two rounds triple-dose albendazole 400 mg) in Lao PDR, where an initial rapid reduction in human taeniasis prevalence was sustained over the 2 years of the study 49,54…”
Section: Multi-host Interventions Via a One Health Approach To Controlmentioning
confidence: 99%
“…While this study confirmed the ability of ultrasound to diagnose larval cysts in live pigs, only a small number of heavily infected animals were examined. Given that the vast majority of infected pigs have only a few cysts in the entire body [1214], the utility of ultrasonography as an adequate screening tool for food safety purposes or for monitoring progress of control programs is doubtful. However, ultrasonography could prove useful for applications in which detection of heavily infected pigs is the goal.…”
Section: Introductionmentioning
confidence: 99%
“…In a small Zambian study, researchers found that 35% of pigs with 100 or more cysts (compared to 0% of pigs with <100 cysts) were positively identified through tongue examination [19]. While more research is needed to confirm this hypothesis, it is likely that the sensitivity of tongue examination increases at even heavier cyst burdens, which can range into the thousands of cysts [1214]. This makes it a reasonable tool for ring-strategy, which aims to identify only the most heavily infected pigs in a community.…”
Section: Introductionmentioning
confidence: 99%